Norfloxacin Induced Cross-Resistance to Fluoroquinolones and Non fluoroquinolone Groups of Antimicrobial Agents in Pseudomonas aeruginosa (Bangladesh Journal of Medical Science, 2016)
Objective: To detect whether development of resistance to norfloxacin promotes development of resistance to other fluoroquinolones.Material and Methods: Four clinical and two environmental isolates of Pseudomonas aeruginosa susceptible to norfloxacin (Minimum Inhibitory Concentration in the range of 0.4?g/ml to 0.84?g/ml) were manipulated in vitro to induce resistance to norfloxacin by means of serial transfer up to 14 times through media containing increasing concentrations of norfloxacin.Results and Discussion: This in vitro manipulation of isolates of P. aeruginosa resulted in increase of MIC from 0.4?g/ml to 0.84?g/ml to 12.5?g/ml to 13.5?g/ml indicating development of resistance to norfloxacin. The antimicrobial susceptibility testing showed a major decrease in the zone diameters of pefloxacin and ofloxacin, and significant decrease in the zone diameters of ciprofloxacin indicating development of cross resistance to other fluoroquinolones. No appreciable change in the zone diameters of non fluoroquinolone groups of antimicrobial agents indicating no development of resistance to structurally unrelated antibiotics.Conclusions: These results indicate that development of resistance to norfloxacin promotes development of resistance to other fluoroquinolones.Bangladesh Journal of Medical Science Vol.15(4) 2016 p.533-537